Increased Knowledge of Parents in Oral and Dental Care in Pre-School Age Children (2-5) Years in TKIT and KBIT Az Zahra - Hastin Ika Indriyastuti; Juni Sofiana; Eni Indrayani (Prosiding University Research Colloquium, 2022)
Preschool children aged 2-5 years have a high percentage of caries problem (40% -75%). The main factor caused by caries in preschool children is the frequency of brushing their teeth, the lack of fluorine water supply, the access to dental health services, diet, and the parents' knowledge about dental and oral health. Parental knowledge should know about their child's dental health, especially a mother. The purpose of this activity is to increase the knowledge of parents in maintaining oral and dental caries in pre-school age children at KBIT and TKIT Az Zahra Karanganyar. The method used in this activity starts from the preparation stage, providing material about dental caries in children and evaluation. Activity assessment was carried out by analyzing the results of the pre-test and post-test questionnaires. The results showed that most parents experienced an increase in knowledge about dental caries in pre-school age children. This activity succeeded in increasing parents' knowledge about dental caries in pre-school age children at KBIT and TKIT Az Zahra Karanganyar